The history of an Indonesian asylee in the Soviet Union / Russian Federation: Sartoyo, 30 years without citizenship (1966–1997) - A.I. Danial (Ученые записки Казанского университета: Серия Гуманитарные науки)
The fate of Sartoyo, an Indonesian asylee among thousands of Indonesian youths who came to study in the USSR in 1962–1965, was studied. His desire was to come back after finishing his studies and use his knowledge for the benefit of his homeland. However, a coup attempt on September 30 – October 1, 1965, which was considered to be planned by the Indonesian Communist Party, changed his fate. This tragedy had a major influence on Sartoyo’s life. Despite the fact that he had not completed his studies yet, Sartoyo, as well as Indonesian students who were abroad, including in the USSR, were ordered to pass an interview procedure at the Indonesian embassy and then return to Indonesia. Those who refused to follow this procedure got their passports revoked, and they, like Sartoyo, became asylees, people with no citizenship. Under this condition, Sartoyo stayed in the USSR / Russian Federation for 30 years and was granted the Russian citizenship in 1997. The sources used in this research were interview materials, conversations and personal testimonies, and legal acts. It was concluded that the life story and experiences of survival of an ordinary person – an eyewitness, an actor, or a victim of political processes – can be summarized by using the oral history methods. The additional sources are used to compare the testimonies. This study can be an alternative source for reconstructing Indonesian historiography after the fall of President Suharto.